THE INFLUENCE OF MENTAL STATE ON THE MOTIVATION OF SERVICEMEN DURING THEIR STAY IN EXTREME AND CRISIS CONDITIONS OF PERFORMING A COMBAT MISSION - Rudenko, Yana (PSYCHOLOGICAL JOURNAL, 2025)
The article draws attention to the problem of the influence of the mental state of servicemen on their motivation in performing combat missions in war. In an extreme environment, where there is a constant threat to life, physical and psycho-emotional exhaustion, the issue of psychological well-being of military personnel is of critical importance. It is the mental state that is a determining factor that affects the level of readiness of a soldier to perform a task, his attitude to service, internal beliefs, self-confidence and ability to overcome difficulties. The paper describes the results of a study among military personnel who are directly performing tasks on the front line. Using a number of standardized methods (including anxiety scales, PTSD, self-assessment of psychophysiological state), the relationship between the psycho-emotional state of the military and the level of their motivation was assessed. The results allowed us to distinguish three groups of servicemen: with a normal mental state, with an acceptable level of non-psychotic symptoms, and with signs of significant psychological disorders. The findings of the study show that higher motivation and readiness for combat is inherent in those whose psycho-emotional state is stable and who have no or minimal signs of mental disorders. Instead, servicemen with high levels of anxiety, depression and PTSD symptoms demonstrate a lower ability to adapt, reduced self-confidence and unwillingness to perform combat missions. Timely detection of disorders, ongoing psychological monitoring and support, as well as systematic work with the motivational sphere of servicemen should become an integral part of training and support for personnel. My experience as a practical psychologist in a military unit confirms that ignoring the signs of exhaustion leads to a loss of combat potential, destruction of internal resources, disorientation in values, and even loss of the meaning of the task. The article emphasises the need to change approaches to assessing the mental state of personnel. It is proposed to integrate regular psychological diagnostics, to strengthen the training of psychologists at the frontline and to focus research on the motivational component in connection with the psycho-emotional state. Thus, this work contributes to a deeper understanding of the mechanisms of influence of non-psychotic mental disorders on the motivation of military personnel. It is believed that further research in this area will help to improve the effectiveness of military units, preserve the mental health of personnel and develop effective rehabilitation and support programmes.